2009
DOI: 10.1088/1674-4926/30/3/034002
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance–voltage characterization of fully silicided gated MOS capacitor

Abstract: This paper investigates the capacitance-voltage (C-V) measurement on fully silicided (FUSI) gated metal-oxide-semiconductor (MOS) capacitors and the applicability of MOS capacitor models. When the oxide leakage current of an MOS capacitor is large, two-element parallel or series model cannot be used to obtain its real C-V characteristic. A three-element model simultaneously consisting of parallel conductance and series resistance or a four-element model with further consideration of a series inductance should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The excellent benefits of organic fluorescent materials in the aforementioned sectors haνe marked the beginning of a new direction of latent fingerprint display research.To obtain effectiνe and sensitiνe latent fingerprint νisualization, many researchers are deνoted to creating new organic fluorescent materials and combining them with established techniques (such as powder brush display, solution immersion method, glue post-fumigation staining method, etc.). Based on the chemical composition of fluorescent organic materials, including both fluorescent organic molecules and fluorescent polymers, the subsequent sections have been categorized into two groups, as outlined in references [13] and [14].…”
Section: Fluorescent Organic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The excellent benefits of organic fluorescent materials in the aforementioned sectors haνe marked the beginning of a new direction of latent fingerprint display research.To obtain effectiνe and sensitiνe latent fingerprint νisualization, many researchers are deνoted to creating new organic fluorescent materials and combining them with established techniques (such as powder brush display, solution immersion method, glue post-fumigation staining method, etc.). Based on the chemical composition of fluorescent organic materials, including both fluorescent organic molecules and fluorescent polymers, the subsequent sections have been categorized into two groups, as outlined in references [13] and [14].…”
Section: Fluorescent Organic Materialsmentioning
confidence: 99%
“…As a transporter, bio affinity enhancer, and fluorescence developer, the matrix utilized by fluorescent organic small molecules for LFP imaging is divided into two groups [13], [14]. Employing diverse methods, such as organic polymers, including conjugated oligomers, polymer dots, and various polymeric matrices, represents a novel category of materials for fluorescence imaging.…”
Section: Materials Dependentmentioning
confidence: 99%
“…The industrial standard error is <4% for MOS capacitance extraction [4]. The three-element model and four-element model are not good enough for very thin di electric layer MOS capacitors because of frequency dispersion and roll-off (or upturn) [5][6][7][8][9][10][11][12]. As the thickness of di electric layer scales down, the impedances are comparable for dielectric layer and interface layer (IL).…”
Section: Introductionmentioning
confidence: 99%
“…These high-frequency capacitance-voltage (C-V) curves will be adjusted with the two-frequency four-element method to eliminate the frequency dispersion effect [3]. From Fig.1, we found that the flat band voltage (VFB) shifts to the lower value as the anneal temperature elevated.…”
mentioning
confidence: 99%